The Significance Of Frnshise - Emeritus, Branislav Djordjevic; Djordjevic, Radomir (Archives of Business Research, 2018)
Any company that aspires in industry must think in terms of global, not domestic market leadership.This chapter focuses on frnachise or expanding beyond domestic bou- ndaries and competing in the market of either a few or a great many countries. In the pr- ocess of exploring these issues, we will introduce a numbere of core concepts. The chap- ter includes section of market expansion, types of franchising, the benefits of buying a frnachise, acquisition, one method of valuaton end etc.